Olympus: An Open-Source Framework For Conversational Spoken Language Interface Research - Bohus, Dan; Raux, Antoine; Harris, Thomas K.; Eskenazi, Maxine; Rudnicky, Alexander I. (HLT-NAACL 2007 workshop on Bridging the Gap: Academic and Industrial Research in Dialog Technology, Rochester, NY, 2007)
We introduce Olympus, a freely available framework for research in conversational interfaces. Olympus’ open, transparent, flexible, modular and scalable nature facilitates the development of large-scale, real-world systems, and enables research leading to technological and scientific advances in conversational spoken language interfaces. In this paper, we describe the overall architecture, several systems spanning different domains, and a number of current research efforts supported by Olympus.